Career Interruptions and Current Earnings: The Role of Interruption Type, Compensation Component, and Gender - Benedikt Gerst; Christian Grund (Institute of Labor Economics (IZA), 2017)
This study examines how career interruptions and subsequent wages of employees are related. Using individual panel data of middle managers from the German chemical sector, we are able to differentiate between different reasons for interruptions as well as between various compensation components. We show that career interruptions are more related to lower subsequent bonus payments than they are to fixed salaries and that interruptions caused by unemployment are associated with higher interruption pay gaps than those resulting from other reasons. In addition, the pay gap after career interruptions is more pronounced for male employees than it is for females.
Keywords: M52; J31; J33; J71; 330; career interruptions; gender pay gap; stigma effects; bonus payments; fixed salaries; total compensation